Formula of the sum of the 1st nth term in a Geometric Progression:
Sum = a₁(1-rⁿ)/(1-r), where a₁ = 1st term, r = common ratio and n= rank nth of term (r≠1)
Sum = (-11)[1-(-5⁸)] /[(1-(-5)]
Sum = (-11)(1- 390625)/(6)
SUM = 716,144
Answer:
2.67
Step-by-step explanation:
This is right trust if not then alright.
Here is the graph! I hope this helps!
Answer:
800 miles
Step-by-step explanation:
Let the number of miles be represented by x
Company A for $110 a day plus $0.80 per mile.
$110 + $0.80 × x
110 + 0.80x
Company B charges $30 a day plus $0.90 per mile to rent the same truck.
$30 + $0.90 × x
30 + 0.90x
110 + 0.80x = 30 + 0.90x
110 - 30 = 0.90x - 0.80x
80 = 0.1x
x = 80/0.1
x = 800 miles
800 miles driven per day makes the rental cost for Company A a better deal than Company B's
G(x)=(x+3)2 we must find x? so x+3=0 x=-3 we transformation -3 on left